2010
DOI: 10.1007/s11666-010-9568-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Helium and Nitrogen Gases on the Properties of Cold Gas Dynamic Sprayed Pure Titanium Coatings

Abstract: This study investigates the effect of propellant gas, helium, and nitrogen during cold spraying of titanium coatings. Coatings were characterized by SEM and were evaluated for their deposition efficiency (DE), microhardness, and porosity. In selected conditions, three particle velocities were investigated in which for each condition, the propelling gasesÕ temperature and pressure were attuned to attain similar particle velocities for each gas. Observations show that loosely bonded particles can be detached by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(52 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…However, the DE was found to reach approximately 90% for the highest particle velocities. Although high DE is expected with titanium, normally much higher velocities than those obtained in this work are required to approach 100% DE (Ref 40,45,72).…”
Section: Results and Discussion Deposition Behavior And Sample Characmentioning
confidence: 71%
See 1 more Smart Citation
“…However, the DE was found to reach approximately 90% for the highest particle velocities. Although high DE is expected with titanium, normally much higher velocities than those obtained in this work are required to approach 100% DE (Ref 40,45,72).…”
Section: Results and Discussion Deposition Behavior And Sample Characmentioning
confidence: 71%
“…Since densification of this powder in other PM processes requires less energy than with spherical powder, it is envisioned that deposition may be possible at lower ranges of parameters than those discussed in the literature ( Ref 13,[39][40][41][42][43][44][45]. Therefore, a large range of temperatures and pressures were tested in order to understand the behavior of this unique powder morphology during the CGDS consolidation process.…”
Section: Cgds Processmentioning
confidence: 99%
“…The results of a study wherein coating layers were made using warm spray process to improve coating properties were also reported; 13) another study attempted the manufacture of high-density coating layers using helium gas instead of the existing nitrogen gas as powder feeding gas during kinetic spraying. 14) Authors have also once tried to manufacture titanium coating layers with good properties by using kinetic spray processes and considering factor variables such as powder shape and nozzle shape. 15) These researchers have conducted a study to manufacture Cu, Ni materials through kinetic spray process at different powder preheating temperatures and showed that coating layer properties such as deposition efficiency, porosity, and hardness could be improved by appropriately controlling powder preheating temperatures.…”
Section: )mentioning
confidence: 99%
“…The range of their application is being expanded to diverse areas such as the aerospace industry, car industry, seawater-resistant materials, petrochemical industry, energy industry, biomedical materials, and sporting goods. 14) Note, however, that the prices of titanium raw materials are high, their shaping methods are limited to rolling and forging at high temperatures due to the characteristics of their HCP (hexagonal closed packed) structure, and they require additional post-heat treatment. 5) Furthermore, due to the high oxygen affinity of titanium, special control is necessary such as vacuum and arcs 6) in the casting process.…”
Section: Introductionmentioning
confidence: 99%
“…Randall German provides analyses of several powder manufacturing systems as well as their resulting microstructures, however his discussion of titanium specifically is limited [6]. The martensitic structure of CP Ti powder is discussed in a pair of works by Wong et al [7,8]. Electron backscatter diffraction (EBSD) and secondary electron imaging (SEI) of large (100 lm) Ti-6Al-4V particles performed by Zhang et al verifies that these particles are mostly martensitic [9].…”
Section: Introductionmentioning
confidence: 99%